Investment Analysis of Waste Heat Recovery System Installations on Ships’ Engines - Eunice O. Olaniyi; Gunnar Prause (MDPI AG, 2022)
This study considers incentive provisions for investment decisions related to waste heat recovery system (WHRS) installations on ships to reduce CO2 emissions and improve ships’ engine efficiency. The economic assessment of WHRS installations in the shipping sector is not widely covered in the literature. A reason for this might be that the conventional financial evaluation of sensitive choices is commonly done through capital budgeting methods, which are not flexible enough to integrate future changes in fuel prices and long-term aspects of other costs. Thus, this work evaluates the WHRS investment using the classical budgeting instruments as well as the real-options approach (a more sophisticated approach) to accommodate the presumed expected future changes in the volatile maritime markets. Following the methodology of triangulation, three case studies of ships with varying operational conditions empirically validate the result to depict the practical use of the real-options evaluation method in investment assessment. The capital budgeting analysis reveals that the investment in maritime WHRS technology is only economically favorable under certain frame conditions projected in the work that shows a more realistic assessment of the project.